(untitled) (Olhar de Professor, 2026)
This article reports the experience of developing the continuing education course “Our Roots: The Indigenous and African Presence in Brazilian Identity”, designed for elementary school educators. The team of authors contributed to content creation and pedagogical coordination, addressing methodological challenges in combining art, traditional cultures, and teacher training. Structured in 9 modules (32h), the course is based on Indigenous and African epistemologies and applies active methodologies and gamification to foster anti-racist education in line with Laws 10.639/03 and 11.645/08. The results highlight the importance of decolonial approaches that recognize traditional cultures and position art as a mediator of inclusive pedagogical practices in the Amazonian context.